2022
DOI: 10.1186/s13578-022-00750-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional landscape of circulating platelets from patients with COVID-19 reveals key subnetworks and regulators underlying SARS-CoV-2 infection: implications for immunothrombosis

Abstract: Background Thrombosis and coagulopathy are pervasive pathological features of coronavirus disease 2019 (COVID-19), and thrombotic complications are a sign of severe COVID-19 disease and are associated with multiple organ failure and increased mortality. Platelets are essential cells that regulate hemostasis, thrombus formation and inflammation; however, the mechanism underlying the interaction between platelets and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…RNF187 gene (E3 ubiquitin-protein ligase RNF187) is involved in transfer of ubiquitin and innate immune response. This gene has been reported to be expressed in platelets from COVID-19 patients [77,78] as observed in the present study. We also noticed that among the shared genes, the hemoglobin complexes and lipid mediators are differentially expressed between the COVID-19 samples and malaria samples (Fig.…”
Section: Transcriptional Signatures Associate With Febrile Patient Of...supporting
confidence: 85%
“…RNF187 gene (E3 ubiquitin-protein ligase RNF187) is involved in transfer of ubiquitin and innate immune response. This gene has been reported to be expressed in platelets from COVID-19 patients [77,78] as observed in the present study. We also noticed that among the shared genes, the hemoglobin complexes and lipid mediators are differentially expressed between the COVID-19 samples and malaria samples (Fig.…”
Section: Transcriptional Signatures Associate With Febrile Patient Of...supporting
confidence: 85%
“… 39 Transcriptomic analysis of platelets from COVID‐19 patients revealed enrichment of pathways including IL‐6, tumor necrosis factor (TNF)‐α, blood coagulation, and hemostasis, suggesting the role of platelet activation in the development of thrombosis. 40 , 41 Postmortem examination of lungs also revealed microvascular thrombi in association with neutrophil extracellular traps (NETs) and platelets, suggesting NET‐triggered thrombosis. 42 As the development of thrombosis has been associated with poor prognosis in hospitalized COVID‐19 patients, early prediction of thrombosis and thromboprophylaxis may improve the clinical outcome.…”
Section: Clinical Features Of Acute Covid‐19 Immunopathologymentioning
confidence: 99%
“…Upon stimulation, the platelets secrete coagulation factors, resulting in the formation of leukocyte–platelet aggregates 39 . Transcriptomic analysis of platelets from COVID‐19 patients revealed enrichment of pathways including IL‐6, tumor necrosis factor (TNF)‐α, blood coagulation, and hemostasis, suggesting the role of platelet activation in the development of thrombosis 40,41 . Postmortem examination of lungs also revealed microvascular thrombi in association with neutrophil extracellular traps (NETs) and platelets, suggesting NET‐triggered thrombosis 42 .…”
Section: Clinical Features Of Acute Covid‐19 Immunopathologymentioning
confidence: 99%
“…[22][23][24] Distinctive changes in the gene-expression profile of circulating platelets of COVID-19 patients have been shown involving the pathways associated with protein ubiquitination, antigen presentation, and mitochondrial dysfunction, 24 suggesting a drastic change in the redox balance and in platelet metabolism leading to platelet activation and to the high thrombotic risk of COVID-19 patients. Another study similarly found in platelets from COVID-19 patients differentially expressed lncRNAs involved in the regulation of hemostasis, platelet activation and the immune response, 25 further confirming that platelet hyperactivation and immune-thrombosis are major players in COVID-19 complications.…”
mentioning
confidence: 67%